Development of Healthy Protein-Rich Crackers Using Tenebrio molitor Flour - Djouadi, Anna (2022)
Entomophagy is still a widespread practice in Africa and Asia, although it is declining due to the westernization of diets. Today, the issue of its rehabilitation is underway; indeed, the nutritional economic and ecological stakes of this consumption are strategic. It can be considered an important way to face the scarcity of natural resources, environmental pressures due to the increasing world population, and demand for protein. Tenebrio molitor larvae flour was recently approved by the European Food Safety Authority (EFSA) as a novel food. The aim of the present work was to create protein-rich healthy cracker from insect flour, achieving the claim “source of protein” with a target market focused on the healthy products for consumption on the go. Contents of T. molitor flour from 2 to 20% (%w/w) were tested, using a previously optimized formulation and the comparison in terms of nutritional, physical, and sensory properties with a standard formulation was performed. T. molitor incorporation allowed an improvement in the nutritional profile of snacks, through an increase of 15% in protein content and an enrichment in minerals (namely potassium, phosphorus, copper, and zinc). The crackers containing a 6% of insect flour were the most appreciated by the panelists. The incorporation of T. molitor induced a reduction in firmness and an increase in crispness, resulting from the impact of the protein on the structure. This aspect has a positive impact with respect of the acceptance of snacks—70% of the panelists consider the possibility to buy the crackers with 6% enrichment. A darkening of the samples with the increase in the incorporation of T. molitor flour was also observed, accompanied by a reduction of about 20% of the L* values. Globally, insect protein can play an important role in redesigning food diets, making them more sustainable, with less environmental impact and equally balanced